Gamma Irradiation Effects on Track Properties of PADC-American Acrylics Track Detector - Dipak Sinha (E-Journal of Chemistry)
Gamma irradiation effects on track properties of Polyallyl Diglycol Carbonate (PADC) track detector (PADC-American Acrylics) are studied in the dose range of 101-106 Gy. It is observed that due to gamma exposure the bulk and track-etch rates of the detector increases. This increase in both etch-rates is more pronounced in post gamma exposed PADC detectors. The etch-rate ratio (S) for both pre and post-gamma exposed detectors decreases with increasing etching temperature at the dose of 106Gy. At a higher etching temperature of 70ºC, the etch rates ratio becomes almost equal for post gamma exposed detector. Etching efficiency of the detector is found to be much higher when exposed to gamma radiation. However it is observed that at the etching temperature of 70ºC, etching efficiency for both pre and post-gamma exposed samples tends to become almost equal to the pristine one.